Embryotoxicity following repetitive maternal exposure to scorpion venom - BN Hmed; B Riadh; H Serria; J Kamel; Z Khaled (Journal of Venomous Animals and Toxins including Tropical Diseases, 2012)
Although it is a frequent accident in a few countries, scorpion envenomation during pregnancy remains scarcely studied. In the present study, the effects of repetitive maternal exposure to Buthus occitanus tunetanus venom are investigated and its possible embryotoxic consequences on rats. Primigravid rats received a daily intraperitoneal dose of 1 mL/kg of saline solution or 300 µg/kg of crude scorpion venom, from the 7th to the 13th day of gestation. On the 21st day, the animals were deeply anesthetized using diethyl-ether. Then, blood was collected for chemical parameter analysis. Following euthanasia, morphometric measurements were carried out. The results showed a significant increase in maternal heart and lung absolute weights following venom treatment. However, the mean placental weight per rat was significantly diminished. Furthermore, blood urea concentration was higher in exposed rats (6.97 ± 0.62 mmol/L) than in those receiving saline solution (4.94 ± 0.90 mmol/L). Many organs of venom-treated rat fetuses (brain, liver, kidney and spleen) were smaller than those of controls. On the contrary, fetal lungs were significantly heavier in fetuses exposed to venom (3.2 ± 0.4 g) than in the others (3.0 ± 0.2 g). Subcutaneous blood clots, microphthalmia and total body and tail shortening were also observed in venom-treated fetuses. It is concluded that scorpion envenomation during pregnancy potentially causes intrauterine fetal alterations and growth impairment.